Impact of Business Students Subconscious in Ethical Decision-Making - Duarte de Almeida, I. (26th International EurOMA Conference 2019 "Operations adding value to society", 2019)
A usual management task in organizations is decision-making, and some of the most critical decisions made by business leaders involve ethical components. Our behavioural-ethics-field research explores the subconscious influence of business students (BS) on ethical decision-making processes by applying cases that report ethical dilemmas. A questionnaire with neutral or non-neutral images acting as subliminal stimuli was administered to 30+30 BS to determine the ethical maturity level in decision-making processes and the subconscious influences in these decisions. Cognitive biases and BS metacognitive strategies were identified when non-neutral images were present. The effects of the subconscious in BS ethical decision-making are discussed.